STRATEGIC INNOVATION AS A TOOL FOR ENHANCING COMPETITIVE EXCELLENCE: A STUDY IN IRAQI CEMENT COMPANIES - Dr. Ali Abdel Qader Mahmoud (Scholar Express Journals, 2026)
This study aims to analyze the role of strategic innovation in enhancing competitive excellence through a field study in the Iraqi cement industry. The study stems from the problem of intensifying competition and the challenges facing this sector. To address this problem and achieve the study's objective, the study population was defined as seven cement factories in Iraq. A questionnaire was designed as the primary data collection tool, and it was distributed to a sample of 345 employees representing various job levels in these factories. The data was analyzed using the Statistical Package for the Social Sciences (SPSS, AMOS). The study adopted a descriptive-analytical approach to interpret the results. The results showed a direct and significant impact of strategic innovation on enhancing competitive excellence, confirming that adopting strategic innovation practices contributes significantly to increasing organizations' ability to achieve superiority and excellence in a changing competitive environment. In light of the results, the study recommends adopting strategic innovation as an integrated approach to achieving competitive excellence, rather than treating its dimensions in isolation, due to its impact on maximizing competitive returns
Keywords: Strategic innovation; competitive excellence; Iraqi cement industry